Courting Power: discussion and analysis of a courtroom-based art installation informed by a legal historical case study. Issue 2 (3rd July 2021) - Latchem, Johannah; Rutherford, Helen
ABSTRACT: Courting Power, a courtroom-based art installation by Johannah Latchem presented in the Guildhall, Newcastle upon Tyne in 2018 explored how the acoustics and architecture of the unique courtroom at the Guildhall silenced or facilitated the voices of those involved in its judicial processes. Artistic and scientific approaches were employed in the investigation of the court's abundant acoustic history and these were linked to a micro-study of the trial and sentence of Margaret Hebbron, a 'woman of the town'. The discussion and analysis of the trial and conviction of Margaret Hebbron were central to the courtroom-based art installation and its development and demonstrate the merits of adopting an integrative approach to encourage resonance, for today's audiences. Both Courting Power, and the discussion in this paper, are cross-disciplinary and draw upon practice-led research in fine art, acoustic science, and legal history.